Some New Exact Solutions of (1+2)-Dimensional Sine-Gordon Equation - Wei-Xiong Chen; Ji Lin (Abstract and Applied Analysis)
We use a generalized tanh function expansion method and a direct method to study the analytical solutions of the (1+2)-dimensional sine Gordon (2DsG) equation. We obtain some new interaction solutions among solitary waves and periodic waves, such as the kink-periodic wave interaction solution, two-periodic solitoff solution, and two-toothed-solitoff solution. We also investigate the propagation properties of these solutions.